Hydrophobically modified poly(acrylic acid) using 3-pentadecylcyclohexylamine: synthesis and rheology - Shedge, A. S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique; Pcrrin, P.; Chassenieux, Christophe; Badiger, Manohar V. (Macromolecular Chemistry and Physics, 2005)
Hydrophobically modified poly(acrylic acid) was synthesized using 3-pentadecylcyclohexylamine (3-PDCA), which was in turn synthesized from 3-pentadecylphenol, one of the components of cashew-nut shell liquid (CNSL), a renewable resource material. H-1 NMR spectra confirmed the incorporation of 3-PDCA onto PAA and a series of HMPs with three different molar concentrations, viz. congruent to 3, 5 and 7 mol-% of 3-PDCA, were synthesized. An increase in viscosity with increasing hydrophobic content was observed by rheological measurements. The critical association concentrations were determined using an Ubbelohde viscometer and a controlled stress rheometer. The stability of HMPs towards temperature and shear was studied. Rheological measurements showed that there was a steady increase in viscosity with increase in hydrophobe content due to the formation of reversible networks. These polymers exhibited gel-like behavior at low concentrations (greater than or equal to2 wt.-%) with an apparent yield stress (ca. 10 Pa) and showed shear thinning properties (non-Newtonian). However, below a critical concentration, c [eta], they showed Newtonian behavior.
Keywords: 3-pentadecylcyclohexylamine (3-PDCA); hydrophobically modified polymers (HMPs); poly(acrylic acid); reversible associations; Rheology

High energy electron irradiation effects on polystyrene films - Mathad, R. D.; Kumar, H. G. Harish; Sannakki, B.; Ganesh, S.; Sarma, K. S. S.; Badiger, Manohar V. (Radiation Effects and Defects in Solids, 2009)
The effect of an 8MeV electron-beam on the structural, optical and dielectric properties of polystyrene films has been investigated respectively by means of Fourier transform infrared (FTIR) spectroscopy, ultraviolet-visible (UV-VIS) spectroscopy and electrical impedance (LCR) analysis over a radiation dose in the range of 50-250kGy using a Microtron accelerator. The FTIR spectral analysis shows no change in the overall structure of the irradiated polystyrene films, except a minor change in the intensity of a few peaks in the FTIR spectrum, indicating that polystyrene is resistant to electron-beam irradiation over the range of radiation doses investigated. The optical band gap analysis using the UV-VIS absorption spectra of the polystyrene shows a small decrease in the optical band gap (Eg) and the activation energy with an increase in electron doses. Further, the dielectric measurements over a frequency range of 100Hz to 1MHz for the electron-beam-irradiated polystyrene films show that both the dielectric constant and the dielectric loss increase with an increase in electron radiation dose, which may be ascribed to the formation of defect sites in the band gap of polystyrene as a consequence of molecular chain scission in the polymer films upon irradiation.
Keywords: electrons; optical spectroscopy; Polymers; radiation

Hydrophobically modified poly(vinyl alcohol) using alkoxy-substituted methyl gallate: synthesis and rheology - Shedge, Aarti S.; Wadgaonkar, Prakash P.; Lele, Ashish K.; Badiger, Manohar V. (Journal of Polymer Science Part B-Polymer Physics, 2010)
Hydrophobically modified poly(vinyl alcohol) (HMPVA) polymers were synthesized by potassium t-butoxide-catalyzed reaction of PVA with methyl 3,4,5-tris(n-octyloxy) benzoate (MGC(8))/3,4,5-tris(n-dodecyloxy) benzoate (MGC(12)) and 1,3-propane sultone. The concentration of 1,3-propane sultone was kept constant at 10 mol %. and that of MGC(8) (2, 3, and 4 mol %)/MGC(12) (2 and 3 mol %) was varied to obtain HMPVAs with different hydrophobic contents. The incorporation of MGC(8)/MGC(12) and 1,3-propane sultone onto HMPVA was confirmed by NMR spectroscopy. Rheological properties of aqueous solutions also confirmed the presence of hydrophobic and charged functional groups on HMPVAs. In the semidilute regime, the specific viscosity of HMPVAs followed concentration scaling that is typical of polyelectrolytes. At higher concentrations, the HMPVA solutions with 3 and 4 mol % of MGC(8) exhibited large increase in specific viscosity. Oscillatory experiments on these solutions exhibited gel-like behavior at polymer concentrations of 40-50 g/L. Confocal microscopy images of HMPVA with 4 mol % of MGC(8) clearly indicated the existence of microgels. The tendency of formation of microgels further increased with increasing chain length of the hydrophobe, that is, with MGC(12). These samples exhibited rheological behavior that is typical of soft solids and was therefore probed by the strain-rate frequency superposition technique reported recently in the literature. HMPVAs with improved rheological properties show potential applications as thickeners in cosmetic creams, lotions and as drug carriers in pharmaceutical formulations. (C) 2010 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 48: 1054-1063, 2010
Keywords: gallic acid; hydrophobically modified poly(vinyl alcohol); Rheology; water-soluble polymers

Hydrophobically Modified Chitosan - Shedge, Aarti S.; Badiger, Manohar V. (Hydrophobically Modified Chitosan, 2014)
Hydrophobically modified chitosan was prepared using the hydrophobic compound derived from natural resource material such as cashew nut shell liquid. Chitosan was modified using 3-pentadecyl cyclohexane carbaldehyde to different extents (2, 3, and 5 mol%). Solution properties of hydrophobically modified chitosan were studied by rheology and light scattering. These indicated the aggregation behavior above the critical association concentration. Further, it was concluded that above the critical association concentration, the dynamics of the network formed due to the associations slowed down significantly.

High-Performance flexible solid-state supercapacitor with an extended nanoregime interface through in situ polymer electrolyte generation - Anothumakkool, Bihag; Torris, Arun A. T.; Veeliyath, Sajna; Vijayakumar, Vidyanand; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
{Here, we report an efficient strategy by which a significantly enhanced electrodeelectrolyte interface in an electrode for supercapacitor application could be accomplished by allowing in situ polymer gel electrolyte generation inside the nanopores of the electrodes. This unique and highly efficient strategy could be conceived by judiciously maintaining ultraviolet-triggered polymerization of a monomer mixture in the presence of a high-surface-area porous carbon. The method is very simple and scalable, and a prototype, flexible solid-state supercapacitor could even be demonstrated in an encapsulation-free condition by using the commercial-grade electrodes (thickness = 150 mu m
Keywords: cyclic voltametry; impedance analysis; in situ polymer generation; interface; polymer electrolyte; supercapacitor

High-performance sultone-modified PVA/PAMPS semi-IPN hydrogels for proton exchange membranes - Patwadkar, Manjusha V.; Illathvalappil, Rajith; Torris, Arun; Francis, Sifa C.; Kurungot, Sreekumar; Badiger, Manohar V. (Journal of Applied Polymer Science, 2026)
Hydrogel membranes composed of poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS) and sultone-modified poly(vinyl alcohol) (PVA) were successfully synthesized and evaluated as promising proton-conducting materials. A key advantage involves the premodification of PVA with 1,3-propane sultone to introduce sulfonic acid groups, thereby imparting proton conductivity to the PVA backbone. This sultone-modified PVA was then physically entangled within a PAMPS cross-linked network to form novel semi-interpenetrating network (semi-IPN) hydrogels. This synergistic design leverages the excellent film-forming and mechanical properties of PVA with the high proton conductivity inherent to PAMPS. The synthesized membranes exhibited robust mechanical properties, with tensile strengths ranging from 5 to 30 MPa and percentage elongations between 200% and 400%, depending on their humidity content. These hydrogel membranes demonstrated proton conductivities ranging from 0.6 to 4.3 x 10-2 S cm-1. The activation energy for proton conduction was found to be as low as 3.5 kJ mol-1, significantly lower than that of the commercial benchmark membrane, Nafion 117 (12 kJ mol-1). These findings underscore the potential of these novel PAMPS/sultone-modified PVA semi-IPN hydrogel membranes for advanced fuel cell applications.
Keywords: batteries and fuel cells; functionalization of polymers; Gels; membranes; polyelectrolytes